Validation Of HPLC Methods For The Quantitative Estimation Of Benzketozone In Substances And Gels - Tillayeva U.M,; Rakhmanova Z.A,; Tillayeva G.U, (The Bioscan, 2025)
The article presents the results of the developed methods of identification and quantitative estimation of benzketozone in the substance and in 3% gels. Identification was carried out using chromatographic method in thin layers of sorbent (TLС) Benzketozone, the high-performance liquid chromatography (HPLC) method was used. The developed methods were validated according to the following parameters: accuracy, linearity, sensitivity and repeatability. Based on the results, it can be concluded that closely developed and tested methods flow between them. We find it appropriate that for further quality control of Benzketozone in soft dosage forms, we developed through TLС and HPLC methods. Methods have been developed for identifying and determining the quantitative content of benzethone in substances and gels by TLС and HPLC methods.The developed methods have been validated and certified in the laboratory.